1998
DOI: 10.1115/1.2818121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NOx, N20, and CO for Lean-Premixed Combustion in a High-Pressure Jet-Stirred Reactor

Abstract: A high-pressure jet-stirred reactor (HP-JSR) has been built and applied to the study of NOx and N2o formation and CO oxidation in lean-Premixed (LPM) combustion. The measurements obtained with the HP-JSR Provide information on how NOx forms in lean-premixed, high-intensity combustion, and provide comparison to NOx data published recently for practical LPM combustors. The HP-JSR results indicate that the NOx yield is significantly influenced by the rate of relaxation of super-equilibrium concentrations of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…All NO data are adjusted to a mean residence time of 3.2 ms, assuming NO yield is proportional to residence time in the lean, atmosphaic pressure JSR operated at constant combustion temperature. This follows from the work of Steele (1995) and Steele et al (1998). The main results of Table 2 are those for NOx, which are discussed below in conjunction with Figures 6 and 7.…”
Section: Resultsmentioning
confidence: 59%
“…All NO data are adjusted to a mean residence time of 3.2 ms, assuming NO yield is proportional to residence time in the lean, atmosphaic pressure JSR operated at constant combustion temperature. This follows from the work of Steele (1995) and Steele et al (1998). The main results of Table 2 are those for NOx, which are discussed below in conjunction with Figures 6 and 7.…”
Section: Resultsmentioning
confidence: 59%
“…He concluded that the concentration of CH radicals is a significant factor affecting the total NO formation. Prompt mechanism is responsible for NO x formation at low temperatures (Dupont and Williams, 1998;Steele et al, 1998). As the name suggests, N 2 O-intermediate NO formation proceeds through a set of reactions involving N 2 O (Miller and Bowman, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This study has been undertaken to determine if a jet-stirred reactor operated in lean-premixed (LP) mode at high pressure could attain well-stirred behavior for NOx formation. Initial work by Steele (1995) and Steele et al (19%) on NOx formation in a high-pressure jet-stirred reactor (1P-JSR) showed this not to be the case That is, the NOx was indicated to form non-uniformly in the reactor, mainly in the inlet jet, rather than uniformly, as in a well-stinted reactor (WSR). However, Steele (1995) only examined residence times of 2.0 and 4.0 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Initial work by Steele (1995) and Steele et al (19%) on NOx formation in a high-pressure jet-stirred reactor (1P-JSR) showed this not to be the case That is, the NOx was indicated to form non-uniformly in the reactor, mainly in the inlet jet, rather than uniformly, as in a well-stinted reactor (WSR). However, Steele (1995) only examined residence times of 2.0 and 4.0 ms. In the present work, a reactor, geometrically similar to Steele's, has been operated at 6.5 atm for residence time as low as 0.5 ms, and examined for WSR formation of NOx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation